Analysis of Reading Comprehension in Narrative Text at Tenth Grade Students - Sri Ninta Tarigan; Merry Yohana Sinaga; Delfi Suriani Sitorus (Universitas of Muhammadiyah Makassar, 2022)
Language is a communication tool used to talk to each other, language can also be used to describe or express someone's feelings. As we know, language has 4 skills: listening, speaking, and writing. Each skill has its own meaning, but the researcher will discuss reading skills which are the process of thinking and obtaining information from a reading text, so that they can derive meaning from the reading text. Therefore, it is very important to learn reading skills in order to obtain important points or reading information from those who do not know to know. This study aims to analyze how many students can and are able to understand the contents of narrative texts. With this, the researcher selected the tenth graders at the Budi Murni Catholic Private High School 2 to be used as samples. This study uses a quantitative approach, the motive is to examine certain samples, with data collection techniques in the form of distributing questionnaires in the form of a Likert scale, then calculating the results of the answer instruments obtained by each student, followed by coding the answer instruments, after which the values are sought: mean, media, and mode, then the reliability test and validity test were carried out with the aim of proving the validity of the student's answer instrument. So it can be concluded based on the results of the analysis obtained by each learning target, 23 respondents found it easier to understand narrative texts after seeing and/or hearing stories with excessive frequency, there were 5 students who were declared fluent. In retelling the narrative text that has been read, 7 students are able to understand the lesson other than with the help of fingers, pens, or others, 7 students are able and as many as 6 respondents are not in a position to understand the narrative text, even though there are a few sentences left in the text.Bahasa merupakan alat komunikasi yang digunakan untuk berkomunikasi atau berbicara satu dengan yang lain, bahasa juga dapat digunakan untuk menggambarkan atau mengungkapkan perasaan seseorang. Seperti yang kita ketahui dalam berbahasa harus memiliki 4 keterampilan : mendengarkan, berbicara, membaca, dan menulis. Keterampilan membaca merupakan proses memperoleh informasi dari suatu teks bacaan, oleh karena itu keterampilan membaca sangat penting untuk dipelajari siswa sehingga dapat memperoleh poin penting atau infomasi dari yang tidak tahu menjadi tahu. Penelitian ini bertujuan untuk menganalisis tentang seberapa banyak siswa yang dapat dan mampu memahami isi bacaan teks naratif. Dengan ini peneliti memilih siswa kelas X di SMA Swasta Katolik Budi Murni 2 untuk menjadi sampelnya. Penelitian ini menggunakan pendekatan deskriptif kuantitatif, motifnya untuk meneliti suatu sampel tertentu, dengan teknik pengumpulan data berupa penyebaran kuesioner dalam bentuk skala likert, kemudian menghitung hasil instrumen jawaban yang diperoleh masing-masing siswa, dilanjut dengan melakukan coding atau pemberian kode terhadap instrumen jawaban, setelah itu mencari hasil nilai dari : mean, media, dan mode, kemudian melakukan uji reliabilitas dan uji validalitas dengan tujuan untuk membuktikan valid tidaknya instrumen jawaban siswa. Sehingga dapat disimpulkan berdasarkan hasil analisis diperoleh frekuensi masing-masing target pembelajaran yaitu 23 responden lebih mudah memahami teks naratif setelah mereka menonton dan/atau mendengar cerita dengan frekuensi yang berlebihan, terdapat 5 siswa yang dapat dinyatakan lancar dalam menceritakan kembali isi teks naratif yang telah dibaca, 7 siswa mampu memahami pembelajaran selain dengan bantuan jari, bolpoin, atau lainnya, 7 siswa mampu dan sebanyak 6 responden tidak dalam posisi untuk memahami narasi teks meskipun ada beberapa kalimat yang tersisa dalam teks.